Identification of key genes in cleft lip with or without cleft palate regulated by miR-199a-5p. (August 2018) - Chen, Gang; Li, Meng-Xue; Wang, Heng-Xue; Hong, Jia-Wei; Shen, Jun-Yu; Wang, Qi; Shi, Qiao-Mei; Ge, Xing; Ding, Zhen; Zhang, Jin-Peng; Xu, Li-Chun
Abstract: Background: Cleft lip with or without cleft palate (CL/P) is one of the most common congenital defects, which etiology involves both genetic and environmental factors. Previous studies have shown that miR-199a-5p may mediate the occurrence of CL/P. However, the key target genes regulated by miR-199a-5p are not clear. In this study, we employed a systematic bioinformatics analysis of target genes regulated by miR-199a-5p which may be involved in CL/P. Methods: The miRBase, Human miRNA tissue atlas, miRecords, miRpathDB, miRWalk, miRTarBase, DIANA-TarBase (v7.0), Literature search, DAVID software, Cytoscape plugin ClueGO + Cluepedia app, MalaCards, TargetScanhuman7.1, Venny 2.1, STRING and GEO databases were comprehensive employed to identify the key genes regulated by miR-199a-5p associated with CL/P. Results: Total 429 experimentally validated target genes were obtained from five miRNAs related databases. Expressions of miR-199a-5p and its experimentally validated target genes were elevated in bone, brain and skin. KEGG pathway analysis revealed that the target genes were enriched in focal adhesion, microRNAs in cancer and hippo signaling pathway. Biological process categorization revealed that significant portions of the target genes were grouped as transcription, DNA-templated. Total eight intersection genes were identified by using MalaCards and TargetScanhuman7.1. The target gene transforming growth factor alpha ( TGFA ) of miR-199a-5p involved in CL/P is screened and verified. Conclusion: MiR-199a-5p may mediate CL/P by regulating key target gene TGFA . The study may contribute to a better understanding of the etiology of CL/P.